2016
DOI: 10.3892/mmr.2016.5200
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of gene expression in fixed colorectal carcinoma samples as a method for biomarker validation

Abstract: Biomarkers have been described as the future of oncology. Modern proteomics provide an invaluable tool for the near-whole proteome screening for proteins expressed differently in neoplastic vs. healthy tissues. However, in order to select the most promising biomarkers, an independent method of validation is required. The aim of the current study was to propose a methodology for the validation of biomarkers. Due to material availability the majority of large scale biomarker studies are performed using formalin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…To explore potential DEGs between tumor tissue and noncancerous tissue, we compared normal tissue, normal matched tissue and paratumor tissue with CRC tissue as control tissue. We integrated 10 datasets from GEO, TCGA-COAD and TCGA-READ and identified robust DEGs, such as SST (35), SLC26A3 (36), and SLC4A4 (37), which have been reported to be diagnostic biomarkers or therapeutic targets for CRC. We used GO and KEGG enrichment analyses to explore the functions of the DEGs identified by overlapping the DEGs in the 3 datasets.…”
Section: Discussionmentioning
confidence: 99%
“…To explore potential DEGs between tumor tissue and noncancerous tissue, we compared normal tissue, normal matched tissue and paratumor tissue with CRC tissue as control tissue. We integrated 10 datasets from GEO, TCGA-COAD and TCGA-READ and identified robust DEGs, such as SST (35), SLC26A3 (36), and SLC4A4 (37), which have been reported to be diagnostic biomarkers or therapeutic targets for CRC. We used GO and KEGG enrichment analyses to explore the functions of the DEGs identified by overlapping the DEGs in the 3 datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Lower expression of FABP1 indicated liver metastasis of CRC. FABP1 expression was observed throughout cancer development [41].…”
Section: The Biological Analysis Of Top Transcriptsmentioning
confidence: 99%
“…Expression of SLC26A3 was also found elevated in the blood sample of colorectal cancer patients, which indicated its potential as a putative biomarker for colon cancer. 54 , 55 Pitule et al showed that high expression of SLC26A2 in tumor tissue predicted a longer overall survival and disease-free interval in colorectal cancer patients, and lower expression of SLC26A2 expression meant longer disease-free interval. 56…”
Section: Role and Regulation Of Slc Family Protein In Digestive Systementioning
confidence: 99%